Validation of academic internet sources: research with teachers and students of UAT campus Victoria - Gómez-Loperena, Susana (Universidad Autónoma de Tamaulipas, 2013)
The Internet as the transmission medium of academic information creates a challenge for communities and institutions of higher education.It is a low cost tool that requires teachers and students to take up new practices for finding and validating academic information sources. The aim of study was to describe and compare the behavior of teachers and undergraduate students to seek academic information online and to validate their digital sources. We surveyed 255 teachers and 333 students, of seven academic units of the Universidad Autónoma de Tamaulipas (UAT), Victoria Campus, in the periods 2011-3 and 2012- 1. Respondents reported 488 mentions of digital sources, which for analysis were categorized according to their origin. The sources were further divided into “generic”, “with name”, and “information seeker”. It was found that teachers contributed only 21.3 % of all mentions of digital sources, 78.6 % were contributed by students. More than half of the teachers reported that they validated the veracity of the sources, while nearly three quarters of the students reported that they did, although only 45% of them stated they already knew it. Teachers did not influence the behavior of their students in the search process of academic sources on the internet and aprocess of experimentation and self learning was given in groups were students showed more skills and interest to perform online searches.